Estimating attendance for breast cancer screening in ethnic groups in London - Møller Henrik; Dixon Steve; Jack Ruth H; Renshaw Christine; Davies Elizabeth A (BMC, 2010)
Abstract Background Breast screening uptake in London is below the Government's target of 70% and we investigate whether ethnicity affects this. Information on the ethnicity for the individual women invited is unavailable, so we use an area-based method similar to that routinely used to derive a geographical measure for socioeconomic deprivation. Methods We extracted 742,786 observations on attendance for routine appointments between 2004 and 2007 collected by the London Quality Assurance Reference Centre. Each woman was assigned to a lower super output (LSOA) based on her postcode of residence. The proportions of the ethnic groups within each LSOA are known, so that the likelihood of a woman belonging to White, Black and Asian groups can be assigned. We investigated screening attendance by age group, socioeconomic deprivation using the Index of Deprivation 2004 income quintile, invitation type and breast screening service. Using logistic regression analysis we calculated odds ratios for attendance based on ethnic composition of the population, adjusting for age, socioeconomic status, the invitation type and screening service. Results The unadjusted attendance odds ratios were high for the White population (OR: 3.34 95% CI [3.26-3.42]) and low for the Black population (0.13 [0.12-0.13]) and the Asian population (0.55 [0.53-0.56]). Multivariate adjustment reduced the differences, but the Black population remained below unity (0.47 [0.44-0.50]); while the White (1.30 [1.26-1.35]) and Asian populations (1.10 [1.05-1.15]) were higher. There was little difference in the attendance between age groups. Attendance was highest for the most affluent group and fell sharply with increasing deprivation. For invitation type, the routine recall was higher than the first call. There were wide variations in the attendance for different ethnic groups between the individual screening services. Conclusions Overall breast screening attendance is low in communities with large Black populations, suggesting the need to improve participation of Black women. Variations in attendance for the Asian population require further investigation at an individual screening service level.